Teknologi Kesehatan Cerdas Di Kota Cerdas : Sistematik Literatur Review - Nadia Azka Huda Prastiwi (APIC, 2020)
A smart city is a city that is able to improve the quality of life of its people through the support of smart technology. In developing a smart city, there is a concept used by Indonesia which discusses the supporting components of a smart city, namely the smart economy, smart society, smart governance, smart government, smart mobility, smart environment, and smart life. Meanwhile, according to research conducted by Oktaria, et al, stated that 83.33% of health services support the development of smart cities. However, until now, health services in this smart city are still experiencing many obstacles, such as types of smart health technology and grey development opportunities. Therefore, this study aims to determine the types of smart technology and development opportunities through a literature review as many as 30 pieces